PENGARUH CUSTOMER EXPERIENCE QUALITY TERHADAP SIKAP MELAKUKAN POSITIVE WORD OF MOUTH (Survei Dilakukan Terhadap Peserta Heritage City Tour CV. Bandung Trails) - Rahman, Irfan Taufik; Gaffar, Vanessa; Yuniawati, Yeni (THE Journal : Tourism and Hospitality Essentials Journal, 2014)
Heritage city tour held by Bandung Trails is one form of existing heritage tourism promotion in Bandung. Relics of historic buildings in colonial times became the attraction offered in the heritage city tour. Enthusiasts of this heritage tourism is still very little. It is apparent from the number of participants who follow the heritage city tour. Therefore, Bandung Trails using strategies customer experience quality to provide a superior experience for each participant. The purpose of this research was to obtain the findings regarding the application of customer experience quality by Bandung Trails against participants of the heritage city tour, the attitude of the participants after following heritage city tour to do positive WOM and influence customer experience quality against the desire to make positive WOM after following heritage city tour. This type of research is descriptive and verifikatif by using cross sectional method. The respondents in this study of 100 respondents came from participants who had followed the heritage city tour by using the technique of sampling, random sampling. In this study, the independent variable are (X) the customer experience quality consisting of helpfulness, value for time, customer recognition, problem solving, personalization, accessibility and competence, while the dependent variable (Y) in this study are positive WOM. Technique of data analysis used path analysis (path analysis) using SPSS 20. The results of this research show that customer experience quality in categories is quite high. The Sub has the highest valuation of the variables is the promise the lowest variable fulfillment while the sub is the value for time. Variable positive WOM in this research is at a high enough categories with the same value on each indicator. In simultaneous trials, showed the existence of the correlation of customer experience quality and positive WOM. Meanwhile, in a partial test, there are two sub-variables of customer experience quality has no effect on positive WOM that is value for time and customer recognition. As for the suggestion to the Bandung Trails is to further enhance the implementation of the value for time and customer recognition so that the wishes of participants doing positive WOM is getting high.